2018
DOI: 10.1016/j.toxrep.2018.01.001
|View full text |Cite|
|
Sign up to set email alerts
|

Moringa oleifera extract (Lam) attenuates Aluminium phosphide-induced acute cardiac toxicity in rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Recent in vitro and in vivo studies using various disease models have substantiated the medicinal benefits associated with moringa, demonstrating its anti-inflammatory, antibacterial, anti-fibrotic, anti-diabetic, and antioxidant properties [ 5 , [8] , [9] , [10] , [11] , [12] , [13] ]. To date, most studies of the health benefits of moringa were conducted with leaves or leaf extracts [ [10] , [11] , [12] , [14] , [15] , [16] ], which have a different chemical composition from seed extracts [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro and in vivo studies using various disease models have substantiated the medicinal benefits associated with moringa, demonstrating its anti-inflammatory, antibacterial, anti-fibrotic, anti-diabetic, and antioxidant properties [ 5 , [8] , [9] , [10] , [11] , [12] , [13] ]. To date, most studies of the health benefits of moringa were conducted with leaves or leaf extracts [ [10] , [11] , [12] , [14] , [15] , [16] ], which have a different chemical composition from seed extracts [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained result is different from observed by Ghorbel, Elwej [31] who found that rats received AlCl 3 (400 ppm) for 21 days via drinking water induced cardiotoxicity. Novaes, Mouro [32] found that three highest doses of Al for 120 days induced heart toxicity and Gouda, El-Nabarawy [33] found that aluminium phosphide caused significant cardiac histopathological changes. These results are quite different than current study due to variation in dose and exposure duration.…”
Section: Discussionmentioning
confidence: 99%
“…High-density lipoprotein (HDL) is the compound containing both lipid and protein, which transport cholesterol to the liver for excretion in the bile. (Kalaiselvi et al, 2015;Gouda et al, 2018). Aluminium (Al) is toxic to humans and animals.…”
Section: Discussionmentioning
confidence: 99%
“…Al is also found in anticaking agents, preservatives, fi llers, coloring agents, emulsifi ers and baking powders. Such extensive use of Al in consumable and non consumable products will certainly lead to Al entry and deposition in human body, (Denise et al, 2007;Verstraeten et al, 2008;Gura, 2010;Thirunavukkarasu et al, 2013;Kalaisevi et al, 2015;Sakr et al, 2017;Konda et al, 2017;Ahmed et al, 2018).…”
Section: Article Informationmentioning
confidence: 99%